(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article introduces the concept of "Phonolistics," a novel approach in linguistics that focuses on cross-linguistic sound patterns and the systemic organization of phonological elements across languages. Phonolistics combines insights from phonology, historical linguistics, cognitive science, and sociolinguistics, aiming to uncover universal principles and the unique variations of sound systems in human languages. It differs from traditional phonology by examining sounds beyond individual languages, enabling broader comparative studies. Key components include identifying cross-linguistic phonological patterns, understanding phonological evolution, and exploring cognitive and social influences on phonology. This interdisciplinary approach provides valuable applications, particularly in language preservation, speech recognition technology, and second-language acquisition. Challenges remain, including the need for comprehensive phonological data and standardized methodologies. Overall, Phonolistics represents a promising field with the potential to enhance linguistic theory, technology, and language preservation efforts